Salud, subjetividad y estudios cualitativos (2022)
The objective of this book is to present the results of the research project on the research on the senses built around the use and non-use of condoms in transgender women and men who have sex with men (MSM) in the cities of Cali and Medellín, as well as the articulation of the postgraduate works that supported this study from different disciplines. The three studies are articulated in the study of health from qualitative methods and the concept of subjectivity from different theoretical perspectives and different empirical verification fields, namely; sexual health, mental health and physical health. The central research focuses on giving an account of the experiences and experiences around the use of condoms in the last two populations mentioned, its objective is to describe subjective productions, specifically the senses built on the use or non-use of condoms. The study gives intelligibility to subjective productions that many times are relegated from quantitative studies, likewise, it discusses the role played by the structure and the agent in these sexual practices without falling into reductionism. The interpretations and conjectures that the research presents are supported not only in the empirical, the researcher’s interpretation, but also in different studies that have developed the subject from different methods and different countries.